Educação em direitos humanos em escolas integrais cidadãs de ensino médio de João Pessoa: aproximações e deslocamentos - Batista, Jéssica Holanda de Medeiros (2022)
The present work has as its theme the Education in Human Rights in basic education, presenting the context of high school integral education schools. The general objective of this study is to analyze the pedagogical proposal of integral education in João Pessoa Citizen Integral Schools, observing the approximations and displacements with Education in Human Rights in the formulation of its Political Pedagogical Projects (PPP). As specific objectives, we seek to contextualize the EDH and the integral education policy at national and state level; to investigate and characterize the profile of integral education politics of the State of Paraíba and to infer about the guidelines of the Pedagogical Political Projects of the Integral Citizen Schools in the city of João Pessoa and their interface with Human Rights Education. Therefore, we raise the following question: how does Human Rights Education impact on the Political-Pedagogical Projects of Integral Citizen High Schools in the city of João Pessoa? In order to answer this question, to carry out this investigation, we resorted to documental research having as sources the legislation relevant to the implementation of schools and their Pedagogical Political Projects, in addition to the National Plans for Education in Human Rights and other educational legislation in the State of Paraíba. In addition, the research was accompanied by a literature review relevant to the topic under study, highlighting the literature on Human Rights Education and Full-Time Education. For data analysis, we opted for Laurence Bardin's content analysis, as it provides a qualitative analysis of the information. Our research concluded that, despite the normative existence of legislation that deals with an EDH proposal for Integral Citizen Schools, there were few advances and achievements in the formal curricular proposals in the educational establishments analyzed.